The relationship between the Roma and the police: a Roma perspective - Hera, Gabor (Policing and society, 2017)
This paper presents a social science research addressing the relationship between police and the largest minority in Hungary, the Roma. This qualitative study reveals that most of Roma experienced police misconduct and held negative attitudes towards police. Such a relationship weakens overall trust in police and hinders effective policing within and with Roma communities. Therefore, this paper addresses the importance of procedural justice in minority policing but at the same time difficulties of its implementation are highlighted.